Konstruksi Makna Budaya Ngopi sebagai Sarana Komunikasi Antarpribadi Remaja - Kinanti Novinka; Rini Rinawati (Bandung Conference Series: Communication Management, 2022)
Abstract. The background of this research is the coffee culture that is popular with the community, especially for teenagers..Researchers want to examine more deeply about the meanings, motives, and experiences of teenagers when drinking coffee. In addition, coffee is also a means of communication, especially interpersonal communication. Communication activities themselves can be done anywhere. One of them with coffee activities. Researchers also want to know how interpersonal communication occurs when drinking coffee. This study uses a qualitative phenomenological method. The theory used in this research is social construction theory. Researchers also set eight informants as sources of information for this study with the category of adolescents aged 19 to 24 years. The results showed that the meaning of coffee for teenagers is the activity of enjoying a cup of coffee while doing certain activities. Teenagers' motives for coffee are as a means of interaction, as a medium of activity, and as entertainment. The coffee experience experienced by teenagers is divided into positive and negative experiences. Meanwhile, in terms of interpersonal communication, communication while “ngopi” are effective for communication activity. Abstrak. Latar belakang penelitian ini adalah budaya ngopi yang semakin digemari masyarakat khususnya para remaja. Saat ini, ngopi bukan hanya sebagai kegiatan untuk menikmati secangkir kopi saja. seiring dengan perkembangan zaman, ngopi kini menjadi satu rutinitas bagi penikmatnya. peneliti ingin mengkaji lebih dalam tentang pemaknaan, motif, dan pengalaman remaja ketika ngopi. Selain itu, ngopi juga menjadi suatu sarana untuk berkomunikasi, khususnya komunikasi antarpribadi. Kegiatan komunikasi sendiri dapat dilakukan dimana saja. Salah satunya dengan kegiatan ngopi. Peneliti juga ingin mengetahui bagaimana komunikasi antarpribadi yang terjadi ketika ngopi. Hasil penelitian menunjukan bahwa makna ngopi bagi remaja adalah kegiatan menikmati secangkir kopi sambil melakukan aktivitas tertentu. Motif remaja untuk ngopi yaitu sebagai sarana interaksi, sebagai medium kegiatan, dan sebagai hiburan. Pengalaman ngopi yang dialami remaja terbagi menjadi pengalaman positif dan negatif. Sedangkan dari sisi komunikasi antarpribadi, adanya interaksi yang terjadi ketika ngopi menunjukan bahwa ngopi bisa menjadi sarana dan kegiatan komunikasi yang efektif khususnya bagi individu.